Some methodological aspects of conducting and evaluating adult health check-up: a systematic review of regulatory public health documentation in the Russian Federation - O. O. Zaharchenko; I. B. Shikina; D. S. Terenteva (Кубанский научный медицинский вестник, 2023)
Background. The Constitution of the Russian Federation and federal laws define the main postulates of the methodology for preventive measures as a priority in the field of public health. Sectoral regulatory legal acts, namely, orders of the Ministry of Health of Russia present the methodology as a system of principles and methods for organizing preventive activities, including health check-ups of the adult population. The effectiveness of the largest preventive measure of the Russian health care system — health check-ups of certain groups of the adult population — depends on the quality and validity of the methodological provisions of the regulatory legal act.Objective. To assess the completeness and objectivity of methodological approaches to conducting and evaluating medical check-ups of certain groups of the adult population, reflected in regulatory legal acts.Methods. The research methodology involved a systematic review of the regulatory documentation of the Russian Federation in the field of health care from January 2012 to December 2022 to verify the basics of the methodology for conducting and evaluating preventive measures for certain groups of the adult population. The information was searched in the database of the ConsultantPlus legal reference system and on the official website of the Ministry of Health (Russian Federation), as well as in the electronic databases of the CyberLeninka and eLIBRARY.RU scientific electronic libraries. The study involved the methods of content analysis, analytical generalization, analogies, and formalization. Data analysis was focused on the organization of the health check-up of the adult population, the evaluation of its performance and effectiveness in accordance with regulatory legal acts, as well as the assessment of the quality of data obtained during the check-up.Results. A dynamic retrospective study of the regulatory framework, including the orders of the Ministry of Health of Russia, both those that have expired and those that are currently in force, identified methodological shortcomings in conducting and evaluating medical check-ups. The methodology for health check-ups of the adult population is reflected in regulatory acts. However, their number exceeds one or several documents, thereby creating a certain complexity in their interpretation and use in practice. The methodology for assessing and monitoring the implementation of health check-ups appears to be poorly defined, since it is based on a single indicator — coverage of the population with preventive check-ups and clinical examinations, thereby failing to reflect the real effect of the largest preventive measure of the state health care system. The issue requires new methodological approaches to conducting and evaluating health check-ups as a whole. The study and evaluation of check-up results is based on the statistical data analysis with imperfect methodology for collecting the data. This negatively affects the quality of statistical data, thereby leading to inadequate interpretation of the data and, as a result, to erroneous management decisions made at all levels of the executive branch.Conclusion. It is advisable to develop general methodology for conducting medical check-ups, and to consider the feasibility of creating an integral indicator for evaluating them. Specialists in the field of health care, as well as in related fields, should be involved for this purpose. A medical health officer should be assigned to coordinate the development of a methodology for organizing, conducting and evaluating health check-ups.